The Global Wealth Chains of Private-Equity-Run Physician Practices - Richard Bůžek; Christoph Scheuplein (Tijdschrift voor economische en sociale geografie, 2022)
Currently, numerous physician practices in industrial and emerging countries are being taken over by private equity firms and integrated into novel physician corporations. This involves private equity firms producing a global wealth chain (GWC) between their investors and the target asset, using offshore financial centres to facilitate tax-avoiding reflux of capital. Moreover, they are opening up ambulatory health care as an asset for capital investment by overcoming previous market barriers to ambulatory health care via a legal construct. In this paper, we trace the spatial links of these finance-side and sector-specific corporate chains based on a capital flow analysis of private equity takeovers of Medical Care Centres (MCCs) in Bavaria, Germany. With our heuristics of a double-layered GWC, which enables the extraction of value from the German health system, we contribute to the emerging GWC debate that aims to conceptualise the complex and often opaque spatialisations of financialisation processes.
Keywords: 330; private equity; global wealth chains; health care; offshore financial centre; Germany; financialisation